Cuantificación del entrenamiento funcional mediante la valoración del esfuerzo percibido en sujetos físicamente activos (2019)
The purpose of the study was to determine the relationship between the session rating of perceived exertion (RPE) and the Edward Index (EI) to quantify the internal load based on the heart rate in high-intensity functional training with physically active subjects. This is a descriptive correlational study with a sample of 16 men and 7 women. The Course-Navette Test was used in the evaluation of the HRMAX and two days after the Karen WOD was used, where each participant had a Polar h7 pulse watch and the subjective perception scale of the session (0-10) was gathered. The EI was calculated based on these data. The statistical analysis was made in the PSPP software (p-value of 0.05), in which a Spearman correlation coefficient was used to relate the RPE and the EI. The relationship between the scale collected in the different postexercise time fragments and the EI was positive and very significant (r = 0.6-0.8; p < 0.01). In conclusion, the RPE is a viable, economic and easily applied method to quantify the internal load in high-intensity functional training with physically active subjects.